The potential of utrophin modulators for the treatment of Duchenne muscular dystrophy. (4th March 2018) - Guiraud, Simon; Roblin, David; Kay, Davies. E.
ABSTRACT: Introduction : Duchenne muscular dystrophy (DMD) is a lethal, X-linked muscle-wasting disease caused by the lack of dystrophin. A few years after the identification of the dystrophin gene, a ubiquitously expressed transcript with high homology to dystrophin was identified leading to the postulate that utrophin might be an effective surrogate to compensate for the lack of dystrophin in dystrophic muscles. Areas covered : We review the utrophin gene, its regulation, the organisation of the corresponding protein and its dynamic expression pattern in comparison with dystrophin. In view of the evidence that utrophin acts as an efficient substitute to dystrophin to prevent the pathology, we describe the therapeutic approaches to modulate utrophin expression. We review the current status in the development of ezutromid, the first small utrophin modulator drug currently tested in DMD patients. Expert opinion : A utrophin based strategy is a highly promising approach applicable to all DMD patients irrespective of their genetic defect. Whereas accurate utrophin and regeneration quantification tools are urgently needed, the foundation of utrophin based therapies, defined 20 years ago, recently delivered first promising results in DMD patients with ezutromid. The field is at an exciting stage on the road of a universal treatment for all DMD patients.